DESAIN MUTU PENDIDIKAN PESANTREN - Siswanto Siswanto (Karsa: Journal of Social and Islamic Culture, 2015)
The existence of Islamic boarding school (pesantren) as an educational in-stitution has a major influence on the life of community, in cultural, educational, and social aspect. Pesantren has become a center of excellence for the development of human resources that has a base of morality in social life. Based on these considerations, pesantren should position itself as a service industry, which provides services according to the desire of customers. To achieve this, schools can adapt the Total Quality Mana-gement (TQM). TQM emphasizes the personal, ethical, cultural, and system quality that are directed to ensure the commitment of every mem-ber of pesantren in continuously quality improvement efforts. It is required that pesantren affirms itself as an educational institution in which construc-tive ideas constantly arise from to frame the pesantren management for the improvement of education quality. Pesantren needs to make strategic efforts to develop the quality design of education. In so doing, it is required to improve various aspects with regard to educational processes in pesantren, namely leadership, curriculum, learning processes, service orientation, and evaluation. This improvement should be done simul-taneously and consistently, resulting in a boarding school education quality design that can accommodate the needs of students and community.Copyright (c) 2015 by KARSA. All right reservedDOI: 10.19105/karsa.v23i2.726